(untitled) (Journal of the College of Education for Women, 2019)
Our life is a test and the eternal life in the afterlife. So we must work well in our life even win paradise, must always remember the death and there is a life after this death and we will be responsible for everything we’ve done in our life. God did not create us vain but for reward, punishment, for this we must have to well prepare for this great day and we have to think about what to do in order to win the paradise.Keywords: paradise, surat al-rahman, preparation.